ChemInform Abstract: Nickel‐Catalyzed Decarbonylative Borylation of Amides: Evidence for Acyl C—N Bond Activation. Issue 48 (10th November 2016) - Hu, Jiefeng; Zhao, Yue; Liu, Jingjing; Zhang, Yemin; Shi, Zhuangzhi
Abstract: A nickel/N‐heterocyclic carbene catalytic system is established for decarbonylative borylation of amides with Bnep2 by C—N bond activation.